2015
DOI: 10.3109/14767058.2015.1048431
|View full text |Cite
|
Sign up to set email alerts
|

The use of angiogenic biomarkers in maternal blood to identify which SGA fetuses will require a preterm delivery and mothers who will develop pre-eclampsia

Abstract: Objective To determine 1) whether maternal plasma concentrations of angiogenic and anti-angiogenic factors can predict which mothers diagnosed with “suspected small-for-gestational-age fetuses (sSGA)” will develop preeclampsia (PE) or require an indicated early preterm delivery (≤ 34 weeks of gestation); and 2) whether risk-assessment performance is improved using these proteins in addition to clinical factors and Doppler parameters. Methods This prospective cohort study included women with singleton pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 204 publications
(114 reference statements)
2
34
0
Order By: Relevance
“…The inflammatory cytokine levels might have been insufficient to upregulate these cell adhesion molecules. MIUH upregulated vWF, VEGF and adiponectin levels, which are known endothelial injury markers and have been reported to be candidate biomarkers for preeclampsia3637. Adiponectin suppresses insulin signaling and the uptake of insulin-stimulated amino acids in the placenta, and its regulation has important implications for nutrient transport in the placenta383940.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory cytokine levels might have been insufficient to upregulate these cell adhesion molecules. MIUH upregulated vWF, VEGF and adiponectin levels, which are known endothelial injury markers and have been reported to be candidate biomarkers for preeclampsia3637. Adiponectin suppresses insulin signaling and the uptake of insulin-stimulated amino acids in the placenta, and its regulation has important implications for nutrient transport in the placenta383940.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Thus, there has been a great deal of interest in whether or not circulating levels of molecules that could have negative effects on the maternal vasculature can be used to predict and/or diagnose PE. 31, 32, 33 …”
Section: Review Of Placental Development and Function In The Contementioning
confidence: 99%
“…The balance of angiogenic and anti-angiogenic factors appears to be key in the establishment of a successful and functional utero-placental circulation (8186). A deficiency in angiogenic factors was first implicated in the pathogenesis of preeclampsia (8795) and subsequently discovered to play a role in SGA/fetal growth restriction (93, 96), fetal death(97, 98), spontaneous preterm labor (99), Ballantyne syndrome (100), twin-to-twin transfusion syndrome (101), etc. During the course of prospective studies, we observed that some patients with a high concentration of endoglin (an anti-angiogenic factor) had a spontaneous preterm delivery (99).…”
Section: Are There Biomarkers That Identify Patients With Suspected Pmentioning
confidence: 99%